Slamming Probability and Impact to Speedboats Hull Based on Seakeeping Motion - Wulandari, Amalia Ika; Syahab, Husein; Adietya, Berlian Arswendo (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
Slamming is a critical dynamic load for small, high-speed craft because repeated hull–wave impacts can generate intense stresses and deformations that threaten structural integrity. This study investigates the probabilistic risk of slamming and the resulting structural response of an aluminium speedboat by integrating seakeeping motion analysis with structural evaluation. First, vessel motions and wave-induced pressures were computed using the Boundary Element Method (BEM) under regular wave conditions with significant heights of 0.125 m, 0.25 m, and 0.50 m. Heave and pitch motions were quantified through Response Amplitude Operators, and their statistics were used to estimate the probability of bottom slamming. The probability associated with pitch increased from 54 % at 0.125 m to 86 % at 0.50 m, showing that pitch is the dominant trigger for slamming. The calculated hydrodynamic pressures were then applied to a detailed Finite Element Method (FEM) model of the aluminium hull to evaluate structural stresses and deformations. As wave height increased from 0.125 m to 0.50 m, the maximum slamming load rose from 2.28 × 10⁻³ MPa to 9.10 × 10⁻³ MPa, causing peak structural stresses to climb from 4.77 MPa to 19.06 MPa and maximum deformations from 0.19 mm to 0.76 mm. Stress concentrations were consistently located on unsupported bottom plating near the bow, while areas reinforced by transverse frames experienced much lower response. These findings demonstrate that both sea-state severity and hull reinforcement layout govern slamming vulnerability, providing practical guidance for strengthening small craft against impulsive wave impacts.